The impact of heavy physical work in the active age on the net present value of long –term care expenditures (Journal of Universal Excellence, 2026)
Research question: In this paper, we set the question how to evaluate the impact of hard labor in working period on the net present value of the expenses for long-term care.Purpose: To this end, we have developed a model of the actuarial net present value of the expenses for long-term care and examined trajectories of decrease of functional capacities in older people who have worked in particularly hard and difficult jobs and those who did not.Method: In three Slovenian homes for the elderly, we studied the age of entry into long-term care according to the lifestyle of the elderly, particularly depending on the type of work at the workplace. We have developed a model for estimating the net present value (NPV) of lifetime costs of long-term care (LTC) for two groups of elderly. For the calculation of expenses, we used current price for home care, assisted living and institutional care for 2016.Results: We found that the NPV of the expenses for long-term care for those who have worked in workplaces where hard labor is required is more than 47% higher than the average cost of care for older people who did not work in particularly hard and difficult jobs.Organization: It highlights the issue of equitable premiums in the practice of mandatory occupational pension scheme for workers in particularly difficult jobs, which is important for employers.Company: When defining equitable contributions for a compulsory occupational pension scheme for workers in particularly hard and difficult jobs, we should also take into account the fact that these workers will also need costly long-term care. Should these workers also be eligible for compulsory long-term care insurance? This is important question both for the employer and for society as a whole.Originality: This is the first model in Slovenia that deals with expenses of long-term care in an integrated way including nursing, social care, and housing expenses.Restrictions / future research: In the model, we used the last published complete mortality tables, published by SURS for 2007 for both populations. It would be necessary specifically to consider whether the mortality of pensioners who have worked in hard and difficult jobs is different from the mortality for whole Slovenian population.
Keywords: long-term care; home care; assisted living; institucional care; expenditure; net present value